The Violence of the Green Revolution : Third World Agriculture, Ecology, and Politics - Shiva, Vandana (Culture of the land., 2016)
The Green Revolution has been heralded as a political and technological achievement unprecedented in human history. Yet in the decades that have followed it, this supposedly nonviolent revolution has left lands ravaged by violence and ecological scarcity. A dedicated empiricist, Vandana Shiva takes a magnifying glass to the effects of the Green Revolution in India, examining the devastating effects of monoculture and commercial agriculture and revealing the nuanced relationship between ecological destruction and poverty. In this classic work, the influential activist and scholar also looks to the future as she examines new developments in gene technology.